Satisfaction of Bangkok Residents on Exposure of Agro-Tourism Review Media on Facebook - Waraporn Boonjaroen; Phatchara Eamkijkarn Sabaijai (My University, 2023)
The purpose of this research was to study the level of satisfaction with the exposure of agritourism review media among Bangkok residents. Through quantitative research, data were collected from 429 Bangkok residents using online questionnaires. The data were then analyzed by descriptive statistical analysis for frequency, percentage, and standard deviation (S.D.). The results showed that most respondents are women with an average age of 37 years old 7 months, an average income of 27,904.98 baht per month, and having a bachelor’s degree, being employed in companies. Furthermore, they are interested in watching agritourism reviews in terms of accommodations such as homestays and farm stays. In addition, the result of satisfaction on the exposure of agritourism review media showed that the high levels of satisfaction are information accessibility and convenience on Facebook with averages of 3.49 (S.D. = 0.413) and 3.47 (S.D. = 0.402), respectively. The presentation and format on Facebook are at a moderate level of satisfaction with an average of 3.32 (S.D. = 0.380).
Keywords: Bachelor; Statistical Analysis; Diverse Aspects of Tourism Research